Annual review of working conditions in the EU 2006-2007 - Giaccone, Mario; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2007)
By the end of 2006, the revision of the Working Time Directive (2003/88/EC) remained unresolved, with the 'opt-out' clause remaining the most divisive issue. This clause allows some Member States to opt out of setting a maximum 48-hour week where individual workers agree to work longer hours. (See the 2005-2006 review (EU0603AR01)1 for previous developments.) Earlier in the year, on 6 April 2006, the European Court of Justice (ECJ) delivered an interpretation of Council Directive 93/104/EC concerning certain aspects of the organisation of working time; the ECJ ruling underlines workers' essential right to annual leave and the obligation on the Member States to ensure that workers' right to benefit from rest breaks is observed (EU0611059I). In one particular case - the Federatie Nederlandse Vakbeweging versus Staat der Nederlanden (Case C- 124/05) - the ECJ ruled that entitlement to paid annual leave is an important principle of EU social law and that it cannot be replaced simply by payment, other than at the termination of an employment relationship.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Labor supply -- European Union countries; Electronic books